A Community-Based Addiction Rehabilitation Electronic System to Improve Treatment Outcomes in Drug Abusers: Protocol for a Randomized Controlled Trial - Wang, Zhe; Chen, Shujuan; Chen, Junning; Xu, Chunfeng; Chen, Zhikang; Zhuang, Wenxu; Li, Xu; Zhao, Min; Haifeng, Jiang (Frontiers in Psychiatry, 2018)
Introduction: Relapse is very common in drug abusers and contributes to a series of negative consequences. Effective addiction treatment exists but there are some problems in the implementation process. Mobile health (mHealth) offers a potential solution to improving recovery outcome for drug abusers in the community. The research team developed a community-based addiction rehabilitation electronic system (CAREs). The primary aim of this study is to explore whether the integrated rehabilitation based on program CAREs promotes drug abusers to keep abstinence. The secondary aim is to evaluate the impact of CAREs on interaction between drug users and service providers, and on addiction-related physical and social functions. Method and analysis: A randomized controlled trial (RCT) will be conducted. The study is a superiority trial with parallel group design. Seventy drug abusers who are newly ordered to undergo community rehabilitation will be recruited from the community in Shanghai. Participants will be 1:1 randomly assigned to receive integrated community rehabilitation by using CAREs or only receiving routine community rehabilitation for 6 months. Corresponding social workers will provide service and monitor their drug use behavior in accordance with the routine work-flow. Outcomes will be assessed at baseline and in the 6th month. The primary outcome is the performance on illicit drug urine test which will be carried out regularly twice per week during the study period. Secondary study outcomes include longest duration of sustained abstinence, days that participants interact with social workers, and the decrease rate of addiction-related issues severity index. Chi-square tests and ANOVAs will be used to compare characteristics of the members of the two groups. GEE will be used to compare the seven dimensions scores of the ASI between groups. Discussion: The study provides evidence for the feasibility and effectiveness of the "CAREs" system through comparing the results of the intervention group with the control group. This paper describes the design and methodology of the study. Ethics and dissemination: The Ethical Board of SMHC approved the study protocol. All participants will present for the informed consent process. After study completion, the results will be published.